PENGUATAN PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL BAGI PESERTA DIDIK DI SEKOLAH - Sakman Sakman; Sri Rahmadani Syam (SUPREMASI: Jurnal Pemikiran, Penelitian Ilmu-ilmu Sosial, Hukum dan Pengajarannya, 2020)
Abstract: This study presents a literature of review on character education, local wisdom and strengthening of character education based on local wisdom for students in schools. Character education is an effort doing in the world of education to instill character values in students which include components of knowledge, awareness or willingness and action to carry out these values in everyday life. Local wisdom is a culture that contains values that are owned by certain communities and in certain places which are used as guidelines for behavior in their everyday life. Strengthening character education based on local wisdom for students in schools can be carried out in two stages, namely (1) integrating the preparation of lesson plans (RPP) on each subject with local wisdom in the local community and (2) integrating the development of learning materials on each subject with local wisdom in the local community. In addition, the process of character formation of students in schools requires support from various parties, such as schools, families and communities so that students have a complete character with noble values. Based on this, it can be concluded that strengthening character education based on local wisdom for students in schools can form the character of students as a whole with noble values in their environment both at school, family and society.Keywords: Character Education, Local Wisdom, Students